APPLICATION OF THE LAW ERADICATION OF CORRUPTION IN THE CASE OF BANKING CRIMES IN THE REGIONAL PUBLIC COMPANY OF BANK PERKREDITAN RAKYAT BANK CIREBON - Kamil, Insan; Prahidayat, Andrey Anandia; Putra, Gilang Pangestu; Firdaus, Fayed Alkadri; Waluyadi, Waluyadi (Jurnal Abdisci, 2025)
Abstract Background. Corruption is a part of special criminal law with different characteristics from general criminal law, especially in terms of procedural law procedures and the substance it regulates. The differences cover various aspects, including special provisions that deviate from the general criminal law norms. Aims. This study aims to determine how the Investigating Prosecutor applies the Law on the Eradication of Corruption in the case of Banking Crimes. Methods. This study uses a normative juridical method and is descriptive, using a qualitative approach to secondary data obtained from literature and documentary studies as the main data, and primary data obtained from interviews as supporting data. Result. The results of the study show that the basis for the Prosecutor's consideration of applying the Law on the Eradication of Corruption in Criminal Cases at Perumda BPR Bank Cirebon includes the politics of Indonesian law in eradicating corruption, the expertise of investigators in uncovering cases, the existence of state financial losses, the status of the suspect's position as an employee salaried by the state, and the fulfillment of elements in Article 2 and Article 3 of the Corruption Law. Conclusion. The Prosecutor's Office is crucial in enforcing the law, proving elements of criminal acts, and ensuring the return of state losses. In this case, the basis for the Prosecutor's consideration in applying the Corruption Crime Law (Corruption Law) in cases of misappropriation of customer funds and documents at Perumda BPR Bank Cirebon includes the politics of Indonesian law in the eradication of corruption Implementation. The government and OJK need to encourage auditor certification for SPI members, especially in financial auditing and forensic investigations. Each BPR is required to have an internal auditor who is competent in detecting financial irregularities, including suspicious transaction analysis.